As diferenciações e transformações sócio-territoriais no espaço agrário das Missões/RS - Haas, Jaqueline Mallmann (2008)
This research aims to investigate the dynamic and the process of differenciation that happened in the agrarian space of the Developmental Regional Council Missões. The region of study is located in the northwest of Rio Grande do Sul State and it is caracterized specially by its eminently agricultural features and the predominance of the familiar agriculture. Methodologically, we used the method of study/analysis of agrarian spaces (territory). It is known as Agrarian Systems Diagnostic Analysis and we also applied the multivariated analysis to complement this research. This research identified two differents agrarian systems historically constructed in the study´s space and the conformation of diferents homogeneous zones based on the criteria of analysis. Using criteria of natural conditions of the environment, it was possible to identify four homogeneous zones. On the other hand, when considering socioeconomical aspects, we identified five homogenous zones. In relation to the differentiation between agriculturists, we established a typology of rural establishment. In this context, we identified categories such as retired, miniagrarian, familiars and employer. In relation to the types of systems of production practiced by the agriculturist, we identified between the employer establishments the predonimant dynamic that is specialized in the grain cultures. The cattle culture have been losing space and importance in those establishments. In the familiar establishment, the milk-cattle culture is the main activity prepoderant. We also can identified that in the system area of agrarian field, it is predominant the employer agriculture. In this context, we have homegenous zones where the cattles still expressive and other in which the specialization of grain activities is dominant. Yet, in the agrarian system there is predonimance of familiar agriculture and small establishments. Generally, even though the non-linear transformation and the different ways of the homogenous zones identified, we expect that, in a medium time, the study area will present a diversified productive matrix. Futhermore, we believe that those results will not reflect in the production units that are following the inverse way, because they will probably become extremely specialized.